2012
DOI: 10.1519/jsc.0b013e318237ea1c
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Isometric Tests of Trunk Flexor Endurance

Abstract: This study was performed to determine the test-retest reliability and the relationship between 2 tests of trunk flexor muscular endurance-a prone bridge and a modified V-sit. Hold times (in seconds) were measured on 60 healthy volunteers from a University community (17 men, 43 women). Both tests were performed at 1-week intervals. The test-retest reliability of each test was assessed with a subgroup of 10 participants during 3 additional testing sessions at 1-week intervals. One examiner collected all data. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…30 Endurance of the anterior trunk muscles was assessed with the patient holding the body in a straight line, supported only by both forearms and feet (front plank position). 16 Endurance of the lateral trunk muscles was quantified with the patient holding the body in a straight line, while supported only by 1 forearm and the feet (sideplank position). 30 The arm used for support was the arm of the involved side, whereas the arm of the uninvolved side was held next to the trunk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…30 Endurance of the anterior trunk muscles was assessed with the patient holding the body in a straight line, supported only by both forearms and feet (front plank position). 16 Endurance of the lateral trunk muscles was quantified with the patient holding the body in a straight line, while supported only by 1 forearm and the feet (sideplank position). 30 The arm used for support was the arm of the involved side, whereas the arm of the uninvolved side was held next to the trunk.…”
mentioning
confidence: 99%
“…Reliability of these tests has been reported to be excellent, with an ICC 3,1 ranging from 0.95 to 0.99 and an SEM ranging from 3.40 to 9.93 seconds. 16,30 Strength Evaluation Eccentric function of the musculature was selected for assessment because of its role in controlling lower-limb movement during weight-bearing activities. Eccentric strength of the hip and knee musculature was quantified in random order, using an isokinetic dynamometer (Biodex Multi-Joint System 2; Biodex Medical Systems, Inc, Shirley, NY).…”
mentioning
confidence: 99%
“…The reliability of the CS tests has been reported: flexor endurance test (ICC=0.98), Biering-Sorensen isometric extensor test (ICC=0.93), and left and rightbridge test (ICC=0.95) (Nesser et al, 2008). In addition, the prone bridge has shown to have a reliability of ICC=0.95 in healthy adults (Durall et al, 2012).…”
Section: Core Stability Testingmentioning
confidence: 99%
“…Core strength was assessed using four tests: a full plank, lateral planks on the right and left sides, and the Biering-Sørensen test for extensor endurance (23). Both the Biering-Sørensen test and plank tests have excellent inter-rater reliability (ICC = 0.8-0.99 and ICC = 0.95, respectively) (23,24). Investigators demonstrated the correct positioning and allowed participants to try.…”
Section: Core Endurancementioning
confidence: 99%